AXIAL CHEMICAL HETEROGENEITY OF CONTINUOUSLY CASTED STEEL INGOTS - Ju. A. Samojlovich; V. I. Timoshpolskij; I. A. Trusova; E. V. Kalinevich (Литьë и металлургия)
The results of theoretical description of the process of the axial chemical heterogeneity formation in continuously cast slug taking into account heat, diffusion and hydrodynamic phenomenon in two-phase zone of hardening steel are given.